REPRESENTATION SCHEME SELF-IMAGE AND BODY IN CHILDREN OF A PUBLIC SCHOOL OF FORTALEZA (Fiep Bulletin - online, 2014)
The aim of this study was to identify the profile of the notion of the body of children aged four to six years old school Municipal Center for Education and Health Project Source. It is a search that is characterized as exploratory descriptive addressing aspects related to the notion of body profile in children from pre -school level from kindergarten. The sample consisted of thirty (30) children. The sample selection was random and independent of sex. For data collection instrument was used as the BPM of Fonseca (1995) to evaluate the profile of the Notion of Body through two sub-factors: self-image and body design. The results reveal that the thirty (30) children who completed all four tests (13%) had Psychomotor Profile apraxic, 12 (40%) were dyspraxic, 13 (43%) had Eupraxico profile and a (3%) had the profile Hiperpraxico. The data collected showed that: the degree of knowledge that children have demonstrated your body is not presented in an integrated and internalized. Thus we suggest the implementation of programs with specific commitments in psychomotor and working a variety of activities and alternatives that establish goals consistent with the needs presented by children.
Keywords: Child; Self-image; body schema.